2021
DOI: 10.1002/slct.202004231
|View full text |Cite
|
Sign up to set email alerts
|

DFT‐PCM Study on Solvolytic Behaviour of N‐alkyl‐X‐pyridinium Ions

Abstract: Using the M06‐2X method and IEFPCM for ethanol, geometries of various N‐benzhydryl‐X‐pyridinium ions and corresponding heterolytic transition structures have been optimized to calculate free energies of activation (▵G≠model) for the model heterolysis of the ions at 25 °C. Very good correlations between ▵G≠model values and corresponding measured ▵G≠ values have made it possible to estimate reliable reactivities of N‐(4,4′‐dimethoxybenzhydryl)‐X‐pyridinium ions in protic solvents as well as nucleofugality parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…[ 9 ] We have previously shown that free energies of activation for the model heterolysis of some N ‐[4,4′‐bis (dimethylamino)benzhydryl]‐X‐pyridinium ions (DMABh‐X‐pyridinium ions), calculated by using the M06‐2X method [ 10 ] in combination with the IEFPCM solvation model [ 11 ] for ethanol, correlate very well with measured free energies of activation for corresponding solvolyses in several hydroxylic solvents and mixtures. [ 12 ] Besides, the inclusion of the reactive 4,4′‐bis (dimethylamino)benzhydryl electrofuge (DMABh electrofuge) in the model reaction enabled optimization of heterolytic transition structures in a very wide range of reactivity. Accordingly, we have employed the same model reaction and computation methods in this study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 9 ] We have previously shown that free energies of activation for the model heterolysis of some N ‐[4,4′‐bis (dimethylamino)benzhydryl]‐X‐pyridinium ions (DMABh‐X‐pyridinium ions), calculated by using the M06‐2X method [ 10 ] in combination with the IEFPCM solvation model [ 11 ] for ethanol, correlate very well with measured free energies of activation for corresponding solvolyses in several hydroxylic solvents and mixtures. [ 12 ] Besides, the inclusion of the reactive 4,4′‐bis (dimethylamino)benzhydryl electrofuge (DMABh electrofuge) in the model reaction enabled optimization of heterolytic transition structures in a very wide range of reactivity. Accordingly, we have employed the same model reaction and computation methods in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown in the previous study that the slight increase in the α‐C–N bond length toward more reactive DMABh‐X‐pyridinium ions is indicative of increasing instability of the ions. [ 12 ] The increase of the electron‐withdrawing ability of substituents on the X‐pyridine moiety of the ionic substrates decreases the amount of the ionic charge in the moiety, which weakens the α‐C–N bond, destabilizes the ionic substrates and, consequently, decreases the free energy barrier to heterolysis. [ 10 ] In addition, the α‐C–N distances for the two transition structures presented in Figure 1 indicate that the heterolytic TS more resembles a reactant as the reactivity, that is, the instability, in the series of the DMABh‐X‐pyridinium ions increases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations